2014
DOI: 10.1002/bmb.20824
|View full text |Cite
|
Sign up to set email alerts
|

Diverse assessment and active student engagement sustain deep learning: A comparative study of outcomes in two parallel introductory biochemistry courses

Abstract: Although there is increasing evidence for a relationship between courses that emphasize student engagement and achievement of student deep learning, there is a paucity of quantitative comparative studies in a biochemistry and molecular biology context. Here, we present a pedagogical study in two contrasting parallel biochemistry introductory courses to compare student surface and deep learning. Surface and deep learning were measured quantitatively by a study process questionnaire at the start and end of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…1 The SPQ was developed by Biggs et al 1 as a way evaluating student learning strategies, and using this information as part of a quality assurance program, identify students who may need assistance, and to evaluate innovations in teaching and assessment. 9 By way of example of evaluating teaching and assessment changes, Bevan et al 10 demonstrated that traditional lectures/examinations encouraged surface learning, whilst student-centered workshops/multiple examinations throughout a biochemistry subject encouraged deep learning. With regard to the health professions, there are numerous examples 3,[11][12][13][14][15][16] where the SPQ and it's more recent incarnation, the revised 2 factor version of the SPQ (R-SPQ-2F), 9 have been used.…”
Section: Introductionmentioning
confidence: 99%
“…1 The SPQ was developed by Biggs et al 1 as a way evaluating student learning strategies, and using this information as part of a quality assurance program, identify students who may need assistance, and to evaluate innovations in teaching and assessment. 9 By way of example of evaluating teaching and assessment changes, Bevan et al 10 demonstrated that traditional lectures/examinations encouraged surface learning, whilst student-centered workshops/multiple examinations throughout a biochemistry subject encouraged deep learning. With regard to the health professions, there are numerous examples 3,[11][12][13][14][15][16] where the SPQ and it's more recent incarnation, the revised 2 factor version of the SPQ (R-SPQ-2F), 9 have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, enhancing student engagement facilitates diversity in understanding, which is an essential and practical step towards the innovation process and also creates a wide range of intellectual and practical skills among students. 10 Further, improving student engagement can augment the transition from surface learning to deep learning 11,14 (figure 2), which is also key to innovation and to professional success.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of engagement can have direct consequences on students' learning as it always leads to superficial rather than deep learning. [14][15][16][17][18] Several approaches have been reported to improve student engagement in lecture sessions. [14][15][16][17][18] , among which were teacher qualities 6 ( Figure 3) and student factors, 12 ( Figure 4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge for tertiary teaching is to establish deep learning with active learning activities such as group work, small group learning, peer-teaching, problem-based learning. Biggs (2003) as cited by Bevan, Chan & Tanner (2014) proposed 'such strategies require a shift of focus from the teacher to the learner, and are considered better suited to the increasing diversity of tertiary students ' (p.474). This describes ways in which learners collaborate reflectively to co-construct new understanding by engaging in open and critical discussion with teachers and their peers.…”
Section: Tertiary Learning Environmentsmentioning
confidence: 99%